When will Quantum Computing Break RSA-3072? - Michal WRONSKI; Lukasz DZIERZKOWSKI (Communications of International Proceedings, 2021)
Since Peter W. Shor has developed a quantum algorithm for discrete logarithm and factorization, constructing a quantum computer, solving real-world cryptography problems began one of the essential things in modern cryptology. In this paper, we estimate when quantum computers will be able to factor 3072-bits RSA modulus. We focus on two different approaches: general-purpose quantum computing and quantum annealing.
Keywords: Cryptanalysis; factorization; RSA; quantum annealing; D-Wave